THE LEVEL OF INCLUSION OF IDEOLOGICAL AND ECONOMIC VALUES IN ISLAMIC EDUCATION BOOKS FOR THE PREPARATORY STAGE (VOCATIONAL) IN THE REPUBLIC OF IRAQ - AHMED , KASIM (Islamic Sciences Journal, 2023)
This study aimed to identify the degree of embedding the ideological and economic values in Islamic education books for the preparatory stage (vocational) in the Republic of Iraq, and the study used the descriptive analytical method. A list of doctrinal and economic values was used in Islamic education books for the preparatory stage of the researcher's preparation as a tool for study, the sample of the study consisted of (40) teachers of Islamic education courses for the preparatory stage in the Republic of Iraq. The study reached several conclusions: the degree of the inclusion of ideological values in the books of Islamic education for the preparatory stage (large) with a mean (3.613), and the degree of the inclusion of economic values in the books of Islamic education for the preparatory stage also (large) with an average of (3.79), the study also proved the existence of statistically significant differences in the opinions of specialists on the degree of the inclusion of educational values in the books of Islamic education for the preparatory stage (vocational) in Iraq, due to the variable of the gender in favor to (female). The study recommended the need to pay attention to the qualification and training of teachers on an ongoing basis, and urged them to the importance of mastery in the provision of scientific information coupled with practical application as much as possible so that education is more influential in the hearts of students. Complementing this study, the study suggested studying the impact of the school physical and social environment on motivating students to have the various educational values ​​they learn in schools and the effect of that environment on learning in general.